(untitled) (Ciudades, 2017)
The rescue of the issue of patrimony in its cultural confinement has been conducted according to patterns of European cities. These pattern sare difficult to apply in other situations; therefore it is important to confront them with the various society transformation processes and its substrate material. The transformation of Guadalajara’s Downtown in the mid-twentieth century represent the virtual elimination of urban heritage of the city, which is a very different example of radical reshaping functional and social space- This is induced by the new regime of accumulation deployed at that time which allows consideration on the meaning of another context, alternatives and opportunities to introduce the heritage dimension in the evolution of the city.